2020
DOI: 10.1017/jog.2020.43
|View full text |Cite
|
Sign up to set email alerts
|

From high friction zone to frontal collapse: dynamics of an ongoing tidewater glacier surge, Negribreen, Svalbard

Abstract: Negribreen, a tidewater glacier located in central eastern Svalbard, began actively surging after it experienced an initial collapse in summer 2016. The surge resulted in horizontal surface velocities of more than 25 m d−1, making it one of the fastest-flowing glaciers in the archipelago. The last surge of Negribreen likely occurred in the 1930s, but due to a long quiescent phase, investigations of this glacier have been limited. As Negribreen is part of the Negribreen Glacier System, one of the largest glacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…The mechanism further resonates as valid in instances where (enthalpy driven) propagation speeds exceed ice flow velocities (e.g. Murray et al, 2003) and in situations where the lower reaches of the glacier are subject to sudden destabilisation after basal water intrusions (Haga et al, 2020). Nevertheless, examples of up-glacier propagation (e.g.…”
Section: Fundamental Processes Within the Enthalpy Frameworkmentioning
confidence: 78%
See 1 more Smart Citation
“…The mechanism further resonates as valid in instances where (enthalpy driven) propagation speeds exceed ice flow velocities (e.g. Murray et al, 2003) and in situations where the lower reaches of the glacier are subject to sudden destabilisation after basal water intrusions (Haga et al, 2020). Nevertheless, examples of up-glacier propagation (e.g.…”
Section: Fundamental Processes Within the Enthalpy Frameworkmentioning
confidence: 78%
“…Since the 1980s, a growing body of research describes a wide range of observed surge behavior that does not fit neatly within one of the two originally suggested categories of surges (e.g. Fowler et al, 2001;Murray et al, 2003;Dunse et al, 2015;Lovell et al, 2018;Haga et al, 2020). Perhaps as a result, the various additions and revisions to initial surging theories suggested by these newer studies often transcend the boundaries between the initially proposed mechanisms; and the once clear distinction between two separate surging regimes somewhat wanes.…”
Section: Introductionmentioning
confidence: 99%
“…After the 2017 peak in surface velocity, they find a gradual slowdown in which the crevassing of the glacier surface, though, further intensified during the years 2018 and 2019. Haga et al (2020) explain this from flow velocity being still high after the peak, which in turn led to continued stretch in the glacier ice. This indicates we can observe increase in backscatter even after the surge velocity peak.…”
Section: Detailed Examplementioning
confidence: 98%
“…As a detailed example we discuss results for Negribreen and Sonklarbreen on the east coast of Spitsbergen, Svalbard. Fig 2a shows a clear increase in radar backscatter between winter 2018 and winter 2019 for Negribreen, which started to surge in late summer 2016 and had surface velocities peak in the melt season of 2017 (Haga et al, 2020). After the 2017 peak in surface velocity, they find a gradual slowdown in which the crevassing of the glacier surface, though, further intensified during the years 2018 and 2019.…”
Section: Detailed Examplementioning
confidence: 98%
“…A final short remark is that in a recent paper, Haga et al (2020) mention the potential importance of an efficient drainage system in the partial freezing of the Negribreen glacier terminus to its bed surface. The rapid erosion in response to surface events in this study could indicate the capacity of a drainage system to adjust rapidly to changes, even in permafrost.…”
mentioning
confidence: 99%